2000
DOI: 10.1046/j.1523-1747.2000.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Arteriovenous Shunting is a Probable Pathogenetic Mechanism in Erythromelalgia

Abstract: Erythromelalgia is a condition consisting of red, warm, and burning painful extremities. Symptoms are relieved by cold and aggravated by heat. A wide variety of etiologic conditions can cause erythromelalgia, but one common pathogenetic mechanism, microvascular arteriovenous shunting, has been hypothesized. The aim of this study was to test this hypothesis. Quantification of skin microvascular perfusion using laser Doppler perfusion imaging and skin temperature at rest and after central body heating was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 25 publications
2
44
0
1
Order By: Relevance
“…In a prospective study, Kalgaard et al (15) reported histopathological findings characterized by capillary proliferation or vascular damage in 31 of 49 specimens, mainly from patients with PEM. These nonspecific alterations indicated the presence of skin hypoxia secondary to increased arteriovenous shunting and insufficient capillary flow, which is compatible with the shunting hypothesis supported by Mørk et al (13,14).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In a prospective study, Kalgaard et al (15) reported histopathological findings characterized by capillary proliferation or vascular damage in 31 of 49 specimens, mainly from patients with PEM. These nonspecific alterations indicated the presence of skin hypoxia secondary to increased arteriovenous shunting and insufficient capillary flow, which is compatible with the shunting hypothesis supported by Mørk et al (13,14).…”
Section: Discussionsupporting
confidence: 87%
“…According to the shunting hypothesis, EM symptoms are caused by tissue hypoxia, which is induced by a maldistribution of skin microvascular blood flow with increased thermoregulatory flow through arteriovenous shunts and an inadequate nutritive perfusion to normal skin capillaries (13,14). If available blood is shunted away from normal skin capillaries, the skin will be hypoxic.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the observations of Kalgaard et al that suggest that erythromelalgia is not an isolated disease but that it is a pattern of response of cutaneous microvasculature 8 In a prospective study Davis et al observed that erythromelalgia is associated with a neuropathy of small fibers and primary vasculopathies, characterized by an intermittent increase of blood flow, hypoxia, and possibly shunts, with increase in local cellular metabolism. 9,11 Due to the hypothesis of shunts, substances that alter the distribution of skin blood flow can improve the cutaneous oxygenation and induce symptoms relief. Aspirin, which inhibits platelet aggregation can quickly relief the secondary symptoms of coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…6 Mork et al 7 also showed reduced skin capillary density during attacks of erythromelalgia. Prospective studies of a group of patients with erythromelalgia suggest a vasculopathy with increased shunting and flow and increased local cell metabolism or a smallfiber neuropathy.…”
Section: Discussionmentioning
confidence: 95%